Old wine in new bottles? Revisiting contract farming after agrarian reform in Zimbabwe. (22nd August 2016) - Sachikonye, Lloyd
ABSTRACT: This contribution explores emerging features of social relations of production as expressed through the contract farming system in Zimbabwe. It seeks to link earlier research on plantation-based outgrower schemes in tea and sugar that were on a modest scale, to contemporary contract farming in tobacco and cotton that has expanded to a relatively large scale in the post-land reform period. The article questions whether the current expansion wave is a qualitatively new process or a variant of 'old wine in new bottles' in terms of relations between growers and large capital. Some themes for research are then outlined potentially to address emerging pertinent issues arising out of contemporary contract farming arrangements.